Avanço máxilo-mandibular e reposicionamento simultâneo dos discos articulares: avaliação tridimensional - Porciúncula, Guilherme Machado da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study assessed three-‐dimensional displacements and adaptive morphological responses following maxillomandibular advancement (MMA) with or without simultaneous repositioning of the temporomandibular joint (TMJ) articular discs. The sample was composed of CBCT files of cone-‐beam computed tomography images from 32 subjects (23 females and 9 males) that were divided into 2 groups: group 1 (n=12) -‐ subjects without disc displacement underwent MMA with no TMJ intervention; group 2 (n=20) – subjects with bilateral disc displacements underwent MMA with simultaneous TMJ articular disc repositioning. An automatic cranial base superimposition method was used to register the CBCT's files in three time points: T1 (pre-‐surgery), T2 (immediate postoperative) and T3 (at least 11 months follow-‐up). To assess surgical changes (T2-‐T1) and adaptive responses (T3-‐T2), the CBCT's files were compared using the shape correspondence (SPHARM-‐PDM) quantitative method. Statistical analysis was performed by means of Student t test and Pearson correlation coeficient. We observed that surgical displacements (T2-‐ T1) were similar in both groups for all the regions of interest, except the condyles that moved in opposite directions; group 1 (superior and posterior) and group 2 (inferior and anterior). In the longest follow up period (T3-‐T2), we observed large individual variability, with smaller magnitude of change in group 2. Sagittal relapses were similar in both groups and less than 20%. We concluded that maxillomandibular surgical advancement is a stable procedure that promotes condylar displacements immediate after surgey. Articular disc repositioning was beneficial since condylar resorption had lower magnitude in group 2 subjects.

O presente estudo avaliou os deslocamentos tridimensionais e as respostas morfológicas adaptativas após avanços maxilo-‐mandibulares (MMA), com e sem reposicionamento simultâneo dos discos articulares. A amostra foi constituída por arquivos tomográficos digitalizados (TCFC), de 32 indivíduos (23 do gênero feminino e 9 do gênero masculino) que foram divididos em 2 grupos: grupo 1 (n=12 e idade média 31,8 anos) -‐ indivíduos com ATMs normais, sem deslocamento dos discos e submetidos ao MMA sem intervenção da ATM; grupo2 (n=20 e idade média 29,8 anos) -‐ indivíduos com sinais e sintomas de desarranjos nas ATMs, com deslocamento bilateral dos discos articulares e submetidos ao MMA com reposicionamento simultâneo dos discos.. Um método automático de sobreposição pela base do crânio foi utilizado para registrar as TCFC em três tempos distintos; T1 (pré-‐cirúrgico), T2 (pós-‐ cirúrgico imediato) e T3 (pós-‐cirúrgico com no mínimo 11 meses de acompanhamento). Para avaliar as mudanças cirúrgicas (T2-‐T1) e as respostas adaptativas (T3-‐T2), as TCFC foram comparadas através do método de correspondência de forma (SPHARM-‐PDM). A análise estatística foi realizada por meio de teste t de Student, para verificar se houveram diferenças estatisticamente significantes entre os dois tipos de cirurgias, e correlações de Pearson para verificar eventuais indicadores de instabilidade. Observou-‐se que os deslocamentos cirúrgicos (T2-‐T1) foram semelhantes em ambos os grupos para todas as regiões de interesse, exceto os côndilos que se moveram em direções opostas; grupo 1 (superior e posterior) e grupo 2 (inferior e anterior). No período de acompanhamento (T3-‐T2), observou-‐se grande variabilidade individual, com menor magnitude no grupo 2. Recidivas sagitais foram semelhantes em ambos os grupos e menores 20%. Concluímos que o avanço maxilo-mandibular é...
Keywords: Cirurgia; Articulação temporomandibular; Má oclusão de Angle Classe II; Temporomandibular joint